Managing artificial intelligence in international business : Toward a research agenda on sustainable production and consumption - Hasan, Rakibul; Ojala, Arto (John Wiley & Sons, 2024)
The collaboration between artificial intelligence (AI) and humans is reshaping international business (IB) management dynamics, aiming to achieve global sustainable development. Recent IB literature indicates that managing AI brings benefits such as better resource reconfiguration, reduced transaction costs, and global sustainable development. However, existing IB literature provides only meager knowledge about the characteristics of AI and how these characteristics can be employed for international expansion at the intersection of sustainable development. In response, our aim is to construct these characteristics by employing directed qualitative content analysis of empirical AI research. Based on our three constructed characteristics of AI, we contribute to current IB literature by providing a framework to balance economic and social goals and utilizing AI for global sustainable development. Further, we provide future IB research themes to guide IB and AI research toward achieving a sustainable production and consumption agenda.
Keywords: global sustainable development; international business; international expansion; sociotechnical theory; artificial intelligence; fi=Kansainvälinen liiketoiminta|en=International Business|